Disseminated tuberculosis after Polatuzumab‐Vedotin based chemoimmunotherapy in a patient with Burkitt's lymphoma - Sarah A. Elkourashy (21632903) (2024)
This report highlights the risk of latent tuberculosis (TB) reactivation after treatment with Polatuzumab Vedotin (PV), Rituximab, and Bendamustine (PBR protocol) despite appropriate chemoprophylaxis. A 48‐year‐old male with refractory Burkitt's lymphoma (BKL) was treated with PBR protocol. At baseline, the patient had a negative QuantiFERON test result, which turned out to be positive prior to starting PBR. He received chemoprophylaxis for 9 months and was compliant with treatment. One year later, he was admitted with COVID‐19 pneumonia and was treated according to the protocol. His symptoms persisted for 1 month. Investigations yielded disseminated TB‐infiltrated bone marrow and pleura. Downstream B‐cell and T‐cell depletion secondary to CD20 and CD79b antagonism may potentially explain the increased risk of TB reactivation associated with the combination of PV and rituximab. Further research is necessary to monitor the risk of TB reactivation among patients receiving a combination of PV and rituximab, especially in endemic areas with high prevalence and incidence of TB. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8838